Internalizing Christian Values in Strengthening Christian Identity in the Posmodern Era (International Journal of Psychosocial Rehabilitation, 2020)
In Old Testament times, one identity or identification of a person is identified by his family; for example, Mephibosheth ibn Saul (2 Sam. 19:24), but sometimes he is identified based on his tribe also; for example, Makhir ibn Manasseh (Num. 32:33), which states of the tribe of Manasseh.